2015
DOI: 10.1039/c5cs00631g
|View full text |Cite
|
Sign up to set email alerts
|

Can we beat the biotin–avidin pair?: cucurbit[7]uril-based ultrahigh affinity host–guest complexes and their applications

Abstract: The design of synthetic, monovalent host-guest molecular recognition pairs is still challenging and of particular interest to inquire into the limits of the affinity that can be achieved with designed systems. In this regard, cucurbit[7]uril (CB[7]), an important member of the host family cucurbit[n]uril (CB[n], n = 5-8, 10, 14), has attracted much attention because of its ability to form ultra-stable complexes with multiple guests. The strong hydrophobic effect between the host cavity and guests, ion-dipole a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
439
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 372 publications
(495 citation statements)
references
References 147 publications
(503 reference statements)
9
439
0
Order By: Relevance
“…To date, the highest binding constants have been achieved using macrocyclic cucurbituril molecules as host systems. 68 Alternative approaches based on synthetic cyclophane systems have the potential advantage that the binding partners can be optically or redox active, 9-12 but they are presently limited by relatively weak association constants in water. 13,14 Recently, we discovered an unusually effective supramolecular process that threaded a tetralactam macrocycle onto a fluorescent squaraine dye (Scheme 1) that was flanked by two long polyethylene glycol (PEG) chains.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the highest binding constants have been achieved using macrocyclic cucurbituril molecules as host systems. 68 Alternative approaches based on synthetic cyclophane systems have the potential advantage that the binding partners can be optically or redox active, 9-12 but they are presently limited by relatively weak association constants in water. 13,14 Recently, we discovered an unusually effective supramolecular process that threaded a tetralactam macrocycle onto a fluorescent squaraine dye (Scheme 1) that was flanked by two long polyethylene glycol (PEG) chains.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 In comparison with CDs, CB[n]s typically have much higher binding affinities and higher selectivity towards a variety of guest molecules. 14,15 Within the CB [n] family, CB [7] has attracted the most attention as a potent drug delivery carrier owing to its superior solubility in water and appropriate size that can form complexes with numerous organic and organometallic guest molecules of biomedical interest. [16][17][18] In addition, it has been demonstrated that CB [7] exhibited little toxicity at sub-mM concentrations or even up to 1 mM concentration in in vitro cellular models.…”
mentioning
confidence: 99%
“…Previous studies suggest that the AM molecule can form very stable host–guest complex with CB7 20. Therefore, this event is expected to drive the release of free spm and reinduce the transition from B‐ to Z‐DNA.…”
Section: Resultsmentioning
confidence: 94%